Formation and profession: reflecting upon a converging road (Praxis Educativa, 2019)
It is hard to see oneself as the research subject. In this paper, we try to uncover the roads that lead to an integral formation, combining personal experiences and the beginning of a professional career as a professor. This formation led to a dynamic and enriching grid of experiences that helped determine the creation of the subject- professor. Through the narration of her own story, a new professor reflects upon different points of focus that allow us to rethink her formation.We stayed away from the classic analysis format and, instead, put the emphasis on the professor, self-interpreted from multireferential perspectives.We conceptualized the formation in its relation to the early stages of a teaching career, from a dynamic and subjective perspective, influenced by opportunities and experiences.
Keywords: journaling; school biography; teaching profession; autoethnography